PENGARUH EXPERIENTIAL MARKETING TERHADAP MINAT BELI ULANG KONSUMEN PADA JASA TRANSPORTASI PERUM DAMRI TRAYEK PONTIANAK-KUCHING - FREN KASMALA B11107099, INENGAH LEO (Jurnal Manajemen Update, 2014)
Purpose of this study was to determine the effect of experiential marketing to consumers re-buying interest on the route transportation services Perum Damri Kuching-Pontianak Number of samples taken in this study of 102 samples of Perum Damri passenger stretch Kuching-Pontianak. This research uses descriptive method and using SPSS 20.0 program in testing the validity, reliability, normality, multicollinearity and multiple linear regression and simultaneous testing and partial in determining the outcome of research. Think variable (X3) is the most dominant variable has a significant effect partially on buying interest re (Y) with a significant value is 0,047 which is much lower than the critical value of 0,05. This means that in partial think (X3) very affected both positively to the re-purchase interest (Y) on transport services Perum Damri stretch Kuching-Pontianak. Â  Keyword: sense, feel, think, relate and Repurchase Intention